Use of modern pedagogical technologies in the transition to acting skills - Ilhom Masalimov (Euro Asian Journal Publishing, 2024)
This article discusses the integration of modern pedagogical technologies to develop acting skills. Based on an analysis of existing literature, he explores the possibilities of innovative methods such as virtual reality, interactive simulations, and online platforms in drama education. The Methods section provides practical guidelines, and the results section discusses the results of the introduction of these technologies. The article concludes with concepts, suggestions and recommendations for the future of acting education.
Keywords: Acting skills; pedagogical technologies; drama education